1991
DOI: 10.1104/pp.96.3.990
|View full text |Cite
|
Sign up to set email alerts
|

Downward Regulation of Photosynthesis and Growth at High CO2 Levels

Abstract: Numerous photosynthesis and growth measurements of sour orange (Citrus aurantium L.) trees maintained in ambient air and air enriched with an extra 300 microliters per liter of CO2 have revealed the C02-enriched trees to have consistently sequestered approximately 2.8 times more carbon than the control trees over a period of three full years. Under field conditions in the natural environment, plants may not experience the downward regulation of photosynthetic capacity typically observed in long-term CO2 enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…1). This gives some support to earlier finding that, even in a resource-limited environment, trees are capable of fixing more carbon in a doubled ambient [CO 2 ] environment, at least during a few years following the initiation of [CO 2 ] treatment (Idso and Kimball 1991, Marek et al 1997, Wang and Kellomäki 1997. The maintenance of high photosynthetic capacity in the Scots pine after four years of exposure may be related to the CO 2 -induced enhancement in the active sink such as leaf area and root absorption (Wang andKellomäki 1997, Kellomäki andWang 2001).…”
Section: Discussionsupporting
confidence: 74%
“…1). This gives some support to earlier finding that, even in a resource-limited environment, trees are capable of fixing more carbon in a doubled ambient [CO 2 ] environment, at least during a few years following the initiation of [CO 2 ] treatment (Idso and Kimball 1991, Marek et al 1997, Wang and Kellomäki 1997. The maintenance of high photosynthetic capacity in the Scots pine after four years of exposure may be related to the CO 2 -induced enhancement in the active sink such as leaf area and root absorption (Wang andKellomäki 1997, Kellomäki andWang 2001).…”
Section: Discussionsupporting
confidence: 74%
“…Because of the extremely low gm of C. aurantium (see also ref. 9), we would expect that this plant would exhibit more response to elevated C02, and this has been reported (8). However, this is probably not a good plant from which to generalize about CO2 responses (8) given that its gm can be so low.…”
Section: Discussionmentioning
confidence: 98%
“…Wolfe (1994) has discussed how when plants are grown in the field with unrestricted rooting volume, the increased photosynthetic capacity is more likely to be maintained. Gunderson et al (1993) found no downward trend in photosynthesis throughout three field seasons in soil-planted white oak and yellow poplar, and Idso & Kimball (1991) working on soilrooted sour orange trees found no evidence of downward regulation of photosynthesis and growth after 3 yr exposure to elevated COg. In our experiment, the relative photosynthesis increase was gradually lost as drought developed (Fig.…”
Section: Discussionmentioning
confidence: 99%